2019
DOI: 10.1038/s41563-019-0482-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-threshold, continuous-wave upconverting lasing from subwavelength plasmons

Abstract: Miniaturized lasers are an emerging platform for generating coherent light for quantum photonics, in-vivo cellular imaging, solidstate lighting, and fast 3D sensing in smartphones 1-3. Continuouswave (CW) lasing at room temperature is critical for integration with opto-electronic devices and optimal modulation of optical interactions 4,5. Plasmonic nanocavities integrated with gain can generate coherent light at sub-wavelength scales 6-9 , beyond the diffraction limit that constrains mode volumes in dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
152
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(160 citation statements)
references
References 43 publications
0
152
0
1
Order By: Relevance
“…These results clarified the long-standing debate over the viability of plasmonics in laser technology and identified situations in which plasmonic lasers have clear practical advantages. Most recently, an experiment suggested that the threshold of a plasmonic laser can be lowered to 70 W cm −2 via a combination of a lattice plasmonic cavity and an upconverting nanoparticle gain material 121 .…”
Section: Development Of Spasers and Plasmonic Nanolasersmentioning
confidence: 99%
“…These results clarified the long-standing debate over the viability of plasmonics in laser technology and identified situations in which plasmonic lasers have clear practical advantages. Most recently, an experiment suggested that the threshold of a plasmonic laser can be lowered to 70 W cm −2 via a combination of a lattice plasmonic cavity and an upconverting nanoparticle gain material 121 .…”
Section: Development Of Spasers and Plasmonic Nanolasersmentioning
confidence: 99%
“…The low thresholds of thesem icrolasers were ascribed to the avalanche-like upconversion mechanism,a long with the spatialo verlap of the upconversionn anocrystals with the WGM microcavity.T hey also demonstrated CW singlemode upconverting lasing at room temperature from NaYF 4 :Yb/Er@NaYF 4 nanocrystals conformally coated on Ag nanopillar arrays, which support as ingle, sharp lattice plasmonic cavity mode ( Figure 10 j-n). [45] These plasmon-nanoarray upconverting lasers exhibit at hreshold orders of magnitude lower than other miniaturized lasers due to intense electromagnetic near-fields localized in the vicinity of the nanopillars.…”
Section: Lanthanide-doped Nanocrystalsmentioning
confidence: 99%
“…28,31 So far, the great majority of the studies have focused on simple geometries, typically realized by Bravais lattices. Despite this, extremely rich physics and unexpected phenomena, such as plasmon [32][33][34] and polariton lasing, 35,36 strong light-matter coupling [37][38][39][40] and quantum phase transitions, [41][42][43] have emerged, making this research area vibrant and fast-growing.…”
Section: Introductionmentioning
confidence: 99%